Pathways to a durable Israeli-Palestinian peace - Ries, Charles P. 1951- (RAND Corporation, 2025)
The authors examine the possibility that the extraordinary costs and destructiveness of the present Israeli-Palestinian conflict could demonstrate to all the urgent need for a path to a durable peace. The authors consider the history of this asymmetrical conflict; identify lessons from attempts to resolve other thorny conflicts; and set out a road map with short-, medium-, and long-term security, governance, economic, physical and social, and international pathways to such a peace. Three characteristics have made this conflict especially difficult to resolve: (1) There are few credible Israeli or Palestinian partners to exert leadership for peace; (2) the territorial claims of both sides are incompatible; and (3) the conflict has attracted much international involvement, not always in support of compromise and peace. The case studies highlight the importance of individual leaders' personal and political commitment to peace and the role of outside individuals. Leaders who can declare that it is time to explore peace can make a dramatic difference. There are also possible advantages of international pressure, even if the two sides are still far apart. The road map to a durable peace is framed around the destination of a "second state" for the Palestinians. The prerequisites require credible leadership from all sides dedicated to peace. Success would be transformative for the region, its peoples, and the wider world. The benefits include restored security for Israelis and Palestinians, a new construct for Palestinian governance over the longer term, and economic and social revival for Gazans and Palestinians in the West Bank
Keywords: Israel-Hamas War, 2023- / Peace; Palestinian Arabs / Gaza Strip; Palestinian Arabs / West Bank; Jewish-Arab relations; Gaza Strip / International status; West Bank / International status; Disaster Recovery Operations; Economic Development; International Diplomacy; Israel; Nation Building; Palestinian Territories; Peacekeeping and Stability Operations; Gaza, Bande de / Statut international; Cisjordanie / Statut international; BUSINESS & ECONOMICS / Development / Economic Development; HISTORY / Middle East / Israel & Palestine; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / Security (National & International); POLITICAL SCIENCE / Terrorism; SOCIAL SCIENCE / Disasters & Disaster Relief; DIPLOMACY.; DISASTER MANAGEMENT.; ECONOMIC DEVELOPMENT.; ISRAEL.; PEACETIME.; POSTWAR.; REGIONAL SECURITY.